2021
DOI: 10.1038/s41467-021-21199-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent African strains of Zika virus display higher transmissibility and fetal pathogenicity than Asian strains

Abstract: The global emergence of Zika virus (ZIKV) revealed the unprecedented ability for a mosquito-borne virus to cause congenital birth defects. A puzzling aspect of ZIKV emergence is that all human outbreaks and birth defects to date have been exclusively associated with the Asian ZIKV lineage, despite a growing body of laboratory evidence pointing towards higher transmissibility and pathogenicity of the African ZIKV lineage. Whether this apparent paradox reflects the use of relatively old African ZIKV strains in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 111 publications
2
106
1
Order By: Relevance
“…Additional studies to cover the extent of the African ZIKV lineage diversity are needed to determine whether this observation can be generalized to other ZIKV African strains, and also to better assess the risk of emergence for the strains that are currently circulating silently in enzootic cycles or in African human populations. It was recently suggested that epidemics caused by African ZIKV strains might be less easily detected than those caused by Asian strains due to their propensity to cause foetal loss rather than birth defects [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies to cover the extent of the African ZIKV lineage diversity are needed to determine whether this observation can be generalized to other ZIKV African strains, and also to better assess the risk of emergence for the strains that are currently circulating silently in enzootic cycles or in African human populations. It was recently suggested that epidemics caused by African ZIKV strains might be less easily detected than those caused by Asian strains due to their propensity to cause foetal loss rather than birth defects [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional vector competence is a cumulative measure, which is monotonically increasing and often described by a logistic function [24,46]. In contrast, our results are highly variable, indicating the process of transmission is likely heterogeneous at the population and individual levels.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, ZIKV AF circulation in mosquitoes and NHPs in sylvatic areas in Brazil was evidenced (Figure 1) (de Almeida et al, 2019-Preprint publication; Alencar et al, 2021). This lineage displayed higher transmissibility in Aedes aegypti than ZIKV AS , and it was also verified to mosquitoes from South American (Aubry et al, 2021). Alencar et al (2021) found Ae.…”
Section: Zika Virus: Epidemiological Profile and A Threat Of New Outbreaksmentioning
confidence: 85%
“…A comparison between the lineages also showed that ZIKV AF induces higher embryo mortality in chicken embryos than ZIKV AS (Willard et al, 2017). Moreover, Aubry et al (2021) observed that ZIKV AF was more pathogenic in immunocompromised adult mice, and in embryos of mice it was observed that intraplacental infection with ZIKV AF caused subcutaneous edema, high levels of infection, and more severe phenotypes, leading to death. A study showed that vertical transmission of ZIKV AF in mice leads to diminished fetal viability and viral RNA can be detected in different fetal tissues, including those related to brain/neurologic development (Vermillion et al, 2017).…”
Section: African Zika Virus Lineage: Experimental Findingsmentioning
confidence: 93%
See 1 more Smart Citation